2022
DOI: 10.1111/ijcs.12786
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID‐19 on changing consumer behaviour: Lessons from an emerging economy

Abstract: The present study investigates the impact of COVID‐19 on Consumers' changing way of life and buying behaviour based on their socio‐economic backgrounds. A questionnaire survey was carried out to understand the impact of COVID‐19 on consumers' affordability, lifestyle, and health awareness and how these effects influenced their buying behaviour. A total of 425 usable responses were analysed using the structural equation modelling considering Consumers' socio‐economic background as exogenous variables and Consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 68 publications
0
38
1
Order By: Relevance
“…Schneider and Leonard (2022) studied consumer compliance of mask wearing and found that those with lower perceived ability to control becoming infected experienced higher anxiety, and higher anxiety in turn led to a higher propensity to wearing a mask. In a sample of 425 adults in India, Das et al (2022) found that some consumers had adopted certain lifestyle changes (e.g., taking up yoga, herbal products, etc.) and, in turn, these consumers wanted more health products and new lifestyle-supporting products.…”
Section: Literature On Pandemic-induced Anxiety Among Consumersmentioning
confidence: 99%
“…Schneider and Leonard (2022) studied consumer compliance of mask wearing and found that those with lower perceived ability to control becoming infected experienced higher anxiety, and higher anxiety in turn led to a higher propensity to wearing a mask. In a sample of 425 adults in India, Das et al (2022) found that some consumers had adopted certain lifestyle changes (e.g., taking up yoga, herbal products, etc.) and, in turn, these consumers wanted more health products and new lifestyle-supporting products.…”
Section: Literature On Pandemic-induced Anxiety Among Consumersmentioning
confidence: 99%
“…Buying sports equipment to do indoor sports activities has increased (Güngördü Belbağ, 2021). Connecting with online yoga classes (Das et al, 2022) is another behavioral change that has shown significant impact on the life style of consumers.…”
Section: Increased Spending On Health Hygienic Products Lifestyle And...mentioning
confidence: 99%
“…Gifting behavior among friends/family has shrinkage enormously (Vladimirova et al, 2022). Research indicated that the most expended products were masks, hand gloves, hand soaps, hand sanitizers (Das et al, 2022), cleaning products, paper tissues, foods, and drinks (Güngördü Belbağ, 2021).…”
Section: Decreased Spending On Luxury Goods Apparel and Home Décormentioning
confidence: 99%
See 1 more Smart Citation
“…This study asserts that a disruptive event in nature will result in a change in consumer purchase habits as well as behavioural substitutions as a result of the pandemic. (Das et al,2022) [19]. 7) There is currently a greater demand for skin care products all around the world since people are more concerned about their appearance.…”
Section: Objectivesmentioning
confidence: 99%